Pelatihan Mendongeng bagi Mahasiswa Praktikan PIAUD Mengajar - Ita Sholichah, Norma; Khofifah, Ratna (Jurnal Aksi Afirmasi, 2025)
This activity is motivated by the needs of several Early Childhood Education Institutions in South Malang which require several learning innovations, preparing prospective educators who are competent and innovative in facing the challenges of early childhood education. One of the important skills that PIAUD students must have is ability to tell stories effectively. Storytelling requires not only good technique but also a deep understanding of the content that is appropriate to children's developmental needs and Islamic educational values. Therefore, a Service Program was carried out in the form of Storytelling Practice for PIAUD teaching students. This is a development of PIAUD teaching activities which involve students who are members of the Education Department Student Association. The results of this training activity with the Dongeng Kepompong studio turned out to be able to make a significant contribution to improving the quality of early childhood education. This can be shown that students practicing the PIAUD study program can apply training activities through storytelling to young children in the southern Malang area, namely at the Gentong Mas touristm, Wajak. This storytelling activity, which was attended by young children from kindergarten and RA from Malang district, gave a positive response to the storytelling activity carried out by practical students from Al-Qolam University, Malang. They expressed satisfaction and were very entertained by several moral messages through the storytelling activity. Keywords: Storytelling Training, PIAUD Teaching